Place of Importance Gestaltung sozialintegrativer Bildungsräume im Kontext von Flucht und Asyl - Harather, Karin (TU Wien Academic Press, 2019)
This book focuses on the special and unique potential that universities have to offer within the context of people fleeing their homes and seeking asylum and integration. Starting with social diversity as a prerequisite for European urban development, an experimental and transdisciplinary approach to the design of socially integrative learning locations and educational spaces is presented as part of an 'Open University'. The publication results from the 'PLACE of IMPORTANCE' teaching and research project, which includes planning, architectural-artistic and social thinking and actions in equal measure with the intention of creating socio-spatial interventions through learning with and from each other and to bring about their transformation into open educational spaces that exist for the long term. The concept that this approach employs has been specifically applied in Neu Marx. One of the largest refugee shelters in the city of Vienna has been built over recent years in this section of the inner-city development area that is the Erdberger Mais. A new setting for TU Wien as an Open University was established in its neighbourhood and at almost the same time with 'OPENmarx'. The implementation and use of OPENmarx as a 'place of importance' has opened up new possibilities for joint activities and learning, which are reflected in this book as examples of new approaches to the sustainable transformation of towns and cities. Against the backdrop of the international education-policy and planning-theory debates about municipal education landscapes, the potential of institutions and regions for innovative learning processes at a university that is opening itself up to society are explored and illustrated on the basis of reference examples with the intention of then outlining the multifaceted activities carried out by the project team in Neu Marx: social spaces were analysed, space-appropriation options tested, short films produced, furniture built, games developed, stories told and much more in conjunction with students, further lecturers and refugees. Finally, a preliminary résumé of the entire development process was drawn up and the associated opportunities and challenges for the implementation of socially integrative processes and locations were summarised. This book also offers background information and atmospheric impressions that have been woven into the publication as graphically highlighted text and image levels.